Ethical Issues of Human Genetic Databases: A Challenge to Classical Health Research Ethics? - Elger, Bernice (Medical Law and Ethics, 2010)
This book compares the new area of biobanking with the tradition of ethically accepted classical research and highlights the distinctive features of existing databases and guidelines. The volume identifies areas of consensus and controversy while investigating the challenges posed to classical health research ethics by the existence of genetic databases, analyzing the reasons for such varying guidelines. The book will be essential to academics, policy-makers and researchers in the field of medical ethics.